2008
DOI: 10.1002/lsm.20635
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation with 780 nm diode laser attenuates inflammatory cytokines but upregulates nitric oxide in lipopolysaccharide‐stimulated macrophages: Implications for the prevention of aneurysm progression

Abstract: These properties of LLLI, with its effects on smooth muscle cells reported previously, may be of profound therapeutic relevance for arterial diseases such as aneurysm where inflammatory processes and weakening of the matrix structure of the arterial wall are major pathologic components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
2
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 28 publications
5
54
2
8
Order By: Relevance
“…This speculation is due to the fact that similar results have been recently reported in a study that showed an increase in network formation with cellular migration stimulating the formation of neurons at the dose of 6.7 J/cm 2 [56], L. Gavish et al (2008) [57] irradiated monocytes/macrophages and found a decrease in IL-1β, IL-10, IL-1α, IL-6 secretion, demonstrating efficacy in the attenuation of inflammatory processes. In osteosarcoma cultures, irradiation with laser at 780 nm (1, 5, and 10 J/cm 2 ) promoted cellular proliferation without altering the ALP synthesis, which demonstrates that this cell type responds to LLLT.…”
Section: Discussionsupporting
confidence: 74%
“…This speculation is due to the fact that similar results have been recently reported in a study that showed an increase in network formation with cellular migration stimulating the formation of neurons at the dose of 6.7 J/cm 2 [56], L. Gavish et al (2008) [57] irradiated monocytes/macrophages and found a decrease in IL-1β, IL-10, IL-1α, IL-6 secretion, demonstrating efficacy in the attenuation of inflammatory processes. In osteosarcoma cultures, irradiation with laser at 780 nm (1, 5, and 10 J/cm 2 ) promoted cellular proliferation without altering the ALP synthesis, which demonstrates that this cell type responds to LLLT.…”
Section: Discussionsupporting
confidence: 74%
“…12 Their studies have shown that LLLT modifies some fundamental aortic aneurysm processes, progressively increasing matrix protein and smooth muscle cell proliferation, as well as secretion and expression of matrix metalloproteinase. Inhibition of gene expression of proinflammatory cytokine interleukin-1β from these cells was also observed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our data taken together confirm previous reports and clinical trials from other laboratories that NIR laser indeed has effects on reducing inflammation. [29][30][31][32] There is evidence that light acts on cells via the NF-kB pathway among others, 16,33 and many reports have demonstrated that light could have different impacts on different cells and tissues, specifically as regards inflammation. Various studies have reported that the immediate effects of light can be regarded in some cases as pro-inflammatory 34 and immunostimulatory, 35 and in other cases as anti-inflammatory 36 and immunosuppressive.…”
mentioning
confidence: 99%